Immunohistochemistry analysis of PSMA expression at prostatic biopsy in high-risk prostate cancer: potential implications for PSMA-PET patient selection - Droghetti, Matteo; Bianchi, Lorenzo; Presutti, Massimiliano; Vetrone, Luigia; Farolfi, Andrea; Mei, Riccardo; Giunchi, Francesca; Degiovanni, Alessio; Mottaran, Angelo; Piazza, Pietro; Cangemi, Danilo; Castellucci, Paolo; et al. (Frontiers in Oncology, 2024)
Introduction Prostate-specific membrane antigen (PSMA) is a transmembrane protein expressed by normal prostatic tissue. Therefore, molecular imaging targeting PSMA (PSMA-PET) has gained particular interest and diffusion for PCa staging and restaging. Several factors may affect PSMA-PET results, and many tools have been proposed to improve patient selection. Furthermore, PSMA expression is not homogeneous among different tissues and within the prostate itself. The aims of this study were to evaluate immunohistochemistry (IHC) features of prostate biopsy samples and to assess their correlation with whole-mount specimens and PSMA-PET parameters. Methods We included consecutive high-risk PCa patients who underwent PSMA-PET for staging proposal at our institution from January 2022 to December 2022. The PET parameters selected were SUVmax, total volume (TV), and total lesion activity (TL). Each patient underwent multiparametric MRI (mpMRI) and fusion-targeted prostate biopsy prior to surgery. IHC analyses were performed on the index lesion cores. IHC visual score (VS) (1, 2, 3) and visual pattern (VP) (membranous, cytoplasmic, and combined) and the percentage of PSMA-negative tumor areas (PSMA%neg) within biopsy cores were evaluated. Results Forty-three patients who underwent robotic radical prostatectomy after PSMA-PET were available for analyses. Concordance between VS and VP at biopsy and final pathology showed a Cohen’s kappa coefficient of 0.39 and 0.38, respectively. Patients with PSMA%neg <20% had a higher concordance in VS and VP (Cohen’s kappa 0.49 and 0.4, respectively). No difference emerged in terms of median PSMA-TV (p = 0.3) and PSMA-TL (p = 0.9) according to VS at biopsy, while median SUVmax was higher in patients with VS 3 (p = 0.04). Higher SUVmax was associated with membranous and combined VP expression (p = 0.008). No difference emerged between patients with PSMA%neg <20% or PSMA%neg >20% on biopsy cores in terms of SUVmax, PSMA-TL, and PSMA-TV (p = 0.5, p = 0.5, and p = 0.9 respectively). Conclusions We found a correlation between IHC VS and VP on targeted biopsy cores and SUVmax at PSMA-PET. However, the correlation between the IHC parameters of biopsy cores and final pathology was not as high as expected. Nevertheless, the presence of PSMA%neg <20% seems to have a better concordance in terms of visual score.